2011
DOI: 10.1029/2011ja016504
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the January 15, 2010, annular solar eclipse on the equatorial and low latitude ionospheric densities

Abstract: annular eclipse crossed the magnetic equator in the middle of the day over India, in a region instrumented with several magnetometers, Total Electron Content stations using GPS data, and an ionosonde located very near the center of the eclipse. With the help of a one-dimensional model appropriate for the region of interest we show that the ionosonde data was consistent with a lower F region plasma that was moving upwards with only modest velocities in the morning hours and moving resolutely downwards in the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
1
46
0
3
Order By: Relevance
“…In other eclipse cases, a reduction ranging from 0.2 to 4 TECU has been reported (Afraimovich et al, 2002;Krankowski et al, 2008). Choudhary et al (2011), for the solar eclipse of 15 January 2010, have reported a larger decrease in the VTEC at Hyderabad as compared to that for Bangalore and Trivandrum, whereas the obscuration at Hyderabad, Bangalore and Trivendrum was 67.5, 77.1 and 84.3 % respectively. The VTEC at Trivendrum recovered to the mean value by 18:00 IST (∼ 2 h and 50 min after the eclipse), whereas at Hyderabad VTEC did not recover even up to 20:00 IST.…”
Section: Annmentioning
confidence: 99%
“…In other eclipse cases, a reduction ranging from 0.2 to 4 TECU has been reported (Afraimovich et al, 2002;Krankowski et al, 2008). Choudhary et al (2011), for the solar eclipse of 15 January 2010, have reported a larger decrease in the VTEC at Hyderabad as compared to that for Bangalore and Trivandrum, whereas the obscuration at Hyderabad, Bangalore and Trivendrum was 67.5, 77.1 and 84.3 % respectively. The VTEC at Trivendrum recovered to the mean value by 18:00 IST (∼ 2 h and 50 min after the eclipse), whereas at Hyderabad VTEC did not recover even up to 20:00 IST.…”
Section: Annmentioning
confidence: 99%
“…There is so far no observational evidence to support this prediction. Aside from the short-lived effect, some studies noted a high occurrence rate of the counter electrojet on the day of eclipse (Tomás et al 2008;Choudhary et al 2011). This seems to be related to the fact that a solar eclipse, by definition, occurs at new moon, which favors the occurrence of the counter electrojet (e.g., Rastogi 1974).…”
Section: Storm Effectmentioning
confidence: 99%
“…As an alternative approach, Choudhary et al (2011) first calculated a linear regression between H and Dst, and then subtracted it from H . Here, we introduce a modified version of this Dst correction technique.…”
Section: Correction For the Dst Fieldmentioning
confidence: 99%
“…It has been discussed earlier by St.-Maurice et al (2011) in terms of eclipsed-induced Pre-reversal-enhancement (PRE) generated through a superposition of the low (cooling) and high pressure (solar heating) wind systems during the eclipse. Later, Choudhary et al (2011) also supported their arguments by retrieving the direction and amplitude of the plasma drift at the equator from a numerical 1-D model.…”
Section: Fig 5 Depicts the F-region Parameters (Top Three Panels) Atmentioning
confidence: 75%
“…The availability of global geomagnetic and interplanetary parameters, local magnetometer, ionosonde, and the large array of GPS receivers gave us an opportunity to investigate these objectives with a modern multi-instrument study. The comprehensive presentations of Rastogi (1989), Choudhary et al (2011), Madhav Haridas and Manju (2012, and Manju et al (2012Manju et al ( , 2014 motivated to investigate the peculiar ionospheric aspects of the exceptional eclipse configuration during the period.…”
Section: Introductionmentioning
confidence: 99%